Oculomotor routines for perceptual judgments - Aizenman, Avi M.; Gegenfurtner, Karl R.; Goettker, Alexander; Justus Liebig University Giessen (My University, 2024)
In everyday life we frequently make simple visual judgments about object properties, for example, how big or wide is a certain object? Our goal is to test whether there are also task-specific oculomotor routines that support perceptual judgments, similar to the well-established exploratory routines for haptic perception. In a first study, observers saw different scenes with two objects presented in a photorealistic virtual reality environment. Observers were asked to judge which of two objects was taller or wider while gaze was tracked. All tasks were performed with the same set of virtual objects in the same scenes, so that we can compare spatial characteristics of exploratory gaze behavior to quantify oculomotor routines for each task. Width judgments showed fixations around the center of the objects with larger horizontal spread. In contrast, for height judgments, gaze was shifted toward the top of the objects with larger vertical spread. These results suggest specific strategies in gaze behavior that presumably are used for perceptual judgments. To test the causal link between oculomotor behavior and perception, in a second study, observers could freely gaze at the object or we introduced a gaze-contingent setup forcing observers to fixate specific positions on the object. Discrimination performance was similar between free-gaze and the gaze-contingent conditions for width and height judgments. These results suggest that although gaze is adapted for different tasks, performance seems to be based on a perceptual strategy, independent of potential cues that can be provided by the oculomotor system.
Keywords: ddc:150